An Investigatory Project of Baking Soda and Vinegar as an Alternative Fire Extinguisher: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Merrick and Omar (2014) note that fire is the rapid oxidation of a material in the exothermic chemical process of combustion, releasing heat, light, and various reaction products. According to the BFP, the top three causes of fires are electrical connection, lighted cigarette butt, and open flame. Fire originating from electrical connections may be triggered by electrical overload, electrical arc, or electrical short circuit. The researcher design used for the study was quantitative experimental research while utilizing purposive sampling techniques. The statistical treatment used for this study was frequency and percentage, weighted mean, and t-test to determine the difference between the two groups of respondents. Using the questionnaire as the research instrument, the researchers surveyed to identify the level of acceptability of the Alternative Fire Extinguisher in terms of construction materials, procedures and design, effectiveness, and presentation. The study's respondents are 5 STEM Teachers and 5 Fire Fighters. The study results regarding construction materials, procedure, design, effectiveness, and presentation are highly acceptable. The overall weighted mean of the Civil Engineers was 121, interpreted as Highly Acceptable, and STEM Teachers had an overall weighted mean of 121, interpreted as Highly Acceptable. The t-computed was 121, and the t-critical was 121. It indicates no significant difference between the assessments of the two groups of respondents.
Keywords: Alternative fire extinguisher; Fire extinguisher; Fire